1985
DOI: 10.1111/j.1469-1809.1985.tb01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the human aryl hydrocarbon hydroxylase gene to the 2q31→2pter region of chromosome 2

Abstract: Analysis of hybrid cells containing fragments of human chromosome 2 has resulted in the regional localization of a gene for aryl hydrocarbon hydroxylase (AHH). Hybrids prepared from a human cell line containing an established translocation have shown that AHH can be localized to the region 2q31----2pter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It is possible that the locus on 2 is a receptor or a regulatory locus but in view of the lack of evidence the designation AHH has been left unchanged. Recent work has supported the original assignment and localized AHH to 2pter-2q31 (Ocraft et al 1985).…”
Section: Confirmations and Regional Localizationmentioning
confidence: 89%
See 1 more Smart Citation
“…It is possible that the locus on 2 is a receptor or a regulatory locus but in view of the lack of evidence the designation AHH has been left unchanged. Recent work has supported the original assignment and localized AHH to 2pter-2q31 (Ocraft et al 1985).…”
Section: Confirmations and Regional Localizationmentioning
confidence: 89%
“…The gene symbols are given at the top of the figure; the references are given by the numbers at the bottom. Davis et al (1983); (16) Rabin et al (1984); (17) Popescu et al (1985); (18) Francke et al (1983); (19) Cook and Hamerton (HGM6); (20) Cousineau et al (1984); (21) Kao et al (1984); (22) Bock et al (1985); (23 Lackner et al (1984); (27) Knott et al (1984); (28) (1) Kanda et al (1983); (2) Kohl et al (1983); (3) Schwab et al (1984) ; (4) (23) Sukhatme et al (1985); (24) Ocraft et al (1985). …”
Section: Note For All Chromosome Diagramsmentioning
confidence: 99%
“…Human studies Cell culture experiments in humans have identified the regulatory Ah locus and assigned it to chromosome 2 (Wiebel et al, 1981;Ocraft et al, 1985). Amsbaugh et al (1986) have isolated the human PI-450 structural locus.…”
Section: Phase II Conjugationmentioning
confidence: 99%
“…Previously described somatic cell fusion studies indicated that the presence of human chromosome 2pter->q22 was required for the AHH inducibility in Balb/cd mouse RAG cells (Brown et al, 1976;Ocraft et al, 1985;Wiebel et al, 1981). Since these initial reports, a number of genes known to play a role in the regulation of AHH activity have been localized, but none of them map to human chromosome 2.…”
Section: Discussionmentioning
confidence: 99%